Cocoa and REDD - Gockowski, J.; Robiglio, Valentina; Muilerman, Sander; Agyeman, N.F.; Asare, R. (2012)
In the humid lowlands of Africa, the expansion of extensive low-input agriculture is the most important driver of tropical deforestation and forest degradation with a negative impact on biodiversity and climate change (Norris et al. 2010; Phalan et al. 2011). A recent global analysis of the climate change impact of agriculture estimated that between 8.64 and 15.1 million km2 of land were spared from the plow as a result of yield gains achieved since 1961 (Burney et al. 2010). These land savings generated avoided greenhouse gas (GHG) emissions representing between 18% and 34% of the total 478 GtC emitted by humans between 1850 and 2005.